2021
DOI: 10.1136/jech-2021-217032
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to unhealthy food and beverage advertising during the school commute in Australia

Abstract: BackgroundFood marketing exposure has the potential to influence children’s dietary behaviours and health status, however, few studies have identified how ‘obesogenic’ the outdoor food marketing environment is along public transport (bus and/or train) or walking routes that children take to school.MethodsAudits of all outdoor advertisements present along likely train, bus and walking routes to 24 secondary schools (ie, 3 routes per school, 72 routes total) were conducted in Perth, Western Australia (WA). The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…For example, many fast food outlets are located close to schools 10 and fast-food outlet density is positively associated with students' discretionary food purchases. 36 Adolescents and school-aged children are also exposed to high levels of marketing of discretionary food and drink products near schools and on the school commute, 14,37 meaning that food environments surrounding schools are not conducive to optimal dietary choices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, many fast food outlets are located close to schools 10 and fast-food outlet density is positively associated with students' discretionary food purchases. 36 Adolescents and school-aged children are also exposed to high levels of marketing of discretionary food and drink products near schools and on the school commute, 14,37 meaning that food environments surrounding schools are not conducive to optimal dietary choices.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many fast food outlets are located close to schools 10 and fast‐food outlet density is positively associated with students' discretionary food purchases 36 . Adolescents and school‐aged children are also exposed to high levels of marketing of discretionary food and drink products near schools and on the school commute, 14,37 meaning that food environments surrounding schools are not conducive to optimal dietary choices. Public health experts have called for comprehensive government regulation to protect children from ubiquitous advertising for discretionary foods in outdoor spaces and on publicly owned assets 13 and to restrict the number of fast food outlets near schools 36 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, students who have pocket money may choose to actively travel, so they can purchase snacks en route. Australian children are exposed to high levels of outdoor advertising for unhealthy food and drink on school routes, 32 with exposure to unhealthy food advertising known to encourage a preference for and purchasing of unhealthy foods by children 33 . International studies have found that among adolescents, active travel is associated with an increased likelihood of consumption of fast food compared to car travel, related to higher fast‐food purchasing opportunities 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%